Nickel release from stainless steel and nickel titanium archwires - An in vitro study - Huma D. Hussain; Sreedevi D. Ajith; Prachi Goel (Elsevier, 2016)
Aims: This study was conducted to evaluate and compare the nickel release from stainless steel and nickel titanium archwires in artificial saliva over three months with the use of simulated fixed orthodontic appliances. Methods and materials: Fifty simulated fixed orthodontic appliances representing half of the dental arch were used for this study. Five groups of ten samples each were made. Group A was the control group without archwires. Groups B and C contained stainless steel archwires from American Orthodontics (Sheboygan, WI, USA) and Dentaurum (Remanium, Ispringen, Germany) respectively. Groups D and E contained NiTi archwires from American Orthodontics (Sheboygan, WI, USA) and copper NiTi from Ormco (Glendora, CA) respectively. The amount of nickel released from the appliances into the artificial saliva were measured after 1 day, 7 days, 1 month, 2 months and 3 months. The mean release from each group was calculated and compared using Kruskal-Wallis test and Mann-Whitney U test. Results: Significant release of nickel was seen in all groups up to the end of first month (p < 0.05), the median values of which were; Control Group A (without archwire); 13.75 ppb, Group B; 15.2 ppb, Group C; 14.16 ppb, Group D; 18.6 ppb, Group E; 17.45 ppb respectively. On comparing the nickel release between all groups at each time interval, the result was not significant (p > 0.05). Conclusion: The highest amount of nickel was released from nickel titanium archwires, however, the quantity of nickel released from both NiTi and stainless steel archwires were not significant. The rate of nickel released was high within the first week and continued up to the first month after which the nickel content was stable in all the groups.